Manufacturing method for double-sided metal-clad laminate

By adjusting the roll distance and controlling pressure during the roll-to-roll manufacturing of double-sided copper-clad laminates, the method addresses the issue of wrinkles and ensures excellent adhesion and appearance, enhancing productivity.

JP7662375B2Active Publication Date: 2025-04-15NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2021058971
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-15
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

During the continuous roll-to-roll manufacturing of double-sided copper-clad laminates, wrinkles can occur on the surface of the laminate due to excessive thickness and mismatched thermal expansion coefficients between the insulating resin layer and the adhesive layer, leading to defective appearance and productivity issues.

Method used

The method involves adjusting the distance between the laminate rolls to a range of 70% to 97% of the total thickness of the double-sided metal-clad laminate and applying thermal compression bonding while controlling the pressure to 1.0 MPa or less, thereby preventing wrinkles and ensuring proper adhesion.

Benefits of technology

This approach effectively prevents wrinkles and ensures excellent adhesion between layers, resulting in a double-sided metal-clad laminate with a good appearance and increased productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662375000001
    Figure 0007662375000001
  • Figure 0007662375000002
    Figure 0007662375000002
  • Figure 0007662375000003
    Figure 0007662375000003
Patent Text Reader

Abstract

To prevent the occurrence of an appearance defect caused by wrinkles when a double-sided metal-clad laminate is continuously manufactured by a roll-to-roll method.SOLUTION: A double-sided metal-clad laminate 100 is manufactured by thermocompression-bonding a first metal-clad laminate 10 and an adhesive layer-attached metal-clad laminate 20A by superimposing the first metal-clad laminate 10 and the adhesive layer-attached metal-clad laminate 20A and continuously passing them between a pair of pressure rolls 40A and 40B. A distance between the pressure rolls 40A and 40B during thermocompression-bonding is adjusted within a range of 70% or more and 97% or less of a total thickness T1 of the double-sided metal-clad laminate 100, from a viewpoint of preventing the occurrence of wrinkles. A pressure during thermocompression-bonding is preferably 1.0 MPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a double-sided metal-clad laminate, which is used as a material for flexible printed circuits (FPCs) and the like used in electronic products. [Background technology]

[0002] FPCs are generally manufactured by etching the copper layer of a copper clad laminate (CCL), which is a laminate of an insulating resin layer and a copper layer, to process the circuit wiring. Known types of CCL used in FPCs include single-sided copper clad laminate (hereinafter referred to as single-sided CCL), in which copper foil is laminated on only one side of the insulating resin layer, and double-sided copper clad laminate (hereinafter referred to as double-sided CCL), in which copper foil is laminated on both sides of the insulating resin layer.

[0003] A known method for producing CCLs is the lamination method, in which a copper foil and a resin film are thermocompressed together using a metal press roll. When producing CCLs using this lamination method, a method has been proposed in which thermocompression is performed with at least one of the pressing rolls covered with a film-like cushioning material (for example, Patent Document 1).

[0004] Regarding the lamination method, when laminating a liquid crystal polymer film and a metal foil, it has been proposed to use a metal press roll having a resin coating layer of fluororubber, silicone rubber or polyimide having a thickness of 0.02 to 5 mm on the surface thereof in order to improve the appearance of the laminate (for example, Patent Document 2).

[0005] Recently, with the advancement of high performance devices, it has become necessary to deal with higher frequencies of transmitted signals. When transmitting high-frequency signals, if there is a large transmission loss in the transmission path, problems such as loss of electrical signals and long signal delay times occur. For this reason, there is a strong demand for suppressing the transmission loss of high-frequency signals in FPCs as well. One approach to suppressing the transmission loss of FPCs is to increase the thickness of the entire insulating resin layer, and therefore, forming the insulating resin layer to a thickness of 50 μm or more is being considered.

[0006] As a method for producing a CCL having a thick insulating resin layer, a method has been proposed in which a step of casting a polyimide precursor solution is repeated multiple times to thicken the insulating resin layer (for example, Patent Document 3). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2020-6685 A (Claims, etc.) [Patent Document 2] JP 2004-358678 A (Claims, etc.) [Patent Document 3] JP 2017-149128 A (Claims, etc.) Summary of the Invention [Problem to be solved by the invention]

[0008] When continuously manufacturing double-sided CCL using the roll-to-roll method, single-sided CCL is sometimes used as the starting material and laminated with other materials to be bonded (adhesive sheets, other single-sided CCL, etc.) in order to increase the thickness of the insulating resin layer. However, when single-sided CCL is introduced between a pair of laminating rolls together with other materials to be bonded by heat and pressure, if the total thickness of the materials to be bonded exceeds 50 μm, wrinkles may appear on the surface of the manufactured double-sided CCL, causing poor appearance, and a solution was needed.

[0009] Therefore, an object of the present invention is to prevent the occurrence of defects in appearance due to wrinkles when double-sided metal-clad laminates are continuously produced by the roll-to-roll method. [Means for solving the problem]

[0010] As a result of intensive research, the inventors of the present invention have found that wrinkles that occur when double-sided CCLs are continuously manufactured by the roll-to-roll method are caused by bending caused by continuous transportation being rolled up during lamination, and that wrinkles are likely to occur when the thermal expansion coefficient of the single-sided CCL used as the material is low, while the thermal expansion coefficient of the thick adhesive layer interposed to increase the thickness of the insulating resin layer is large. They have also found that the above problem can be solved by performing thermocompression bonding while taking into account the clearance between a pair of pressure rolls when manufacturing double-sided metal-clad laminates by the roll-to-roll method, and have completed the present invention.

[0011] That is, the method for producing a double-sided metal-clad laminate according to the first aspect of the present invention comprises the steps of: A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on one surface of the first metal layer; a single-sided metal-clad laminate with an adhesive layer, the single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on one side of the second metal layer, the single-sided metal-clad laminate having an adhesive layer laminated on the side opposite the second metal layer; The method comprises overlapping the first insulating resin layer and the adhesive layer so that they are in contact with each other, and laminating the layers by continuously passing them between a pair of laminating rolls to produce a double-sided metal-clad laminate. The manufacturing method for a double-sided metal-clad laminate according to the first aspect of the present invention is characterized in that the distance between the pair of lamination rolls is adjusted to within a range of 70% or more and 97% or less of the thickness of the double-sided metal-clad laminate.

[0012] In the method for producing a double-sided metal-clad laminate according to a first aspect of the present invention, the adhesive layer-attached single-sided metal-clad laminate may be obtained via a step of applying and drying a resin composition to a surface of the second single-sided metal-clad laminate opposite the second metal layer to form the adhesive layer.

[0013] A method for producing a double-sided metal-clad laminate according to a second aspect of the present invention comprises: A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on one surface of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on one surface of the second metal layer; a self-supporting adhesive film; The method comprises laminating the first insulating resin layer and the second insulating resin layer so that the adhesive film is interposed between them, and continuously passing the layers between a pair of laminating rolls to produce a double-sided metal-clad laminate. The second aspect of the present invention relates to a method for manufacturing a double-sided metal-clad laminate, and is characterized in that the distance between the pair of lamination rolls is adjusted to within a range of 70% or more and 97% or less of the thickness of the double-sided metal-clad laminate.

[0014] In a second aspect of the present invention, there is provided a method for producing a double-sided metal-clad laminate, comprising the steps of: A step of applying a resin composition to a substrate and drying the composition to form a self-supporting film; peeling the self-supporting film from the substrate; It may be obtained via

[0015] In the method for producing a double-sided metal-clad laminate according to the first and second aspects of the present invention, the pressure applied by the pair of laminating rolls may be 1.0 MPa or less.

[0016] In the method for producing a double-sided metal-clad laminate according to the first and second aspects of the present invention, at least one of the pair of laminating rolls may be a covering roll having a covering layer made of an elastic body on the surface of a metal roll. Effect of the Invention

[0017] According to the present invention, when producing a double-sided metal-clad laminate by the roll-to-roll method, the distance between a pair of lamination rolls is adjusted to within a range of 70% to 97% of the thickness of the double-sided metal-clad laminate, and excessive pressure is not applied to the material to be pressed during thermocompression bonding, thereby effectively preventing the occurrence of wrinkles. Therefore, according to the method of the present invention, it is possible to efficiently produce a double-sided metal-clad laminate that has excellent interphase adhesion, is wrinkle-free, and has a good appearance, and the productivity of double-sided metal-clad laminates can be increased. [Brief description of the drawings]

[0018] [Figure 1] 1A to 1C are diagrams illustrating a method for manufacturing a double-sided metal-clad laminate according to a first embodiment of the present invention. [Diagram 2] 4 is a diagram illustrating the distance between a pair of pressure rolls. [Diagram 3] FIG. 2 is an explanatory diagram showing a cross-sectional structure of a double-sided metal-clad laminate manufactured in the first embodiment. [Figure 4] FIG. 2 is a schematic process diagram of a method for manufacturing a double-sided metal-clad laminate according to the first embodiment. [Diagram 5] 5 is a diagram illustrating a method for producing a double-sided metal-clad laminate according to a second embodiment of the present invention. [Figure 6A] 5 is a schematic process diagram of a method for manufacturing a double-sided metal-clad laminate according to a second embodiment. FIG. [Figure 6B] FIG. 6B is a schematic process diagram illustrating a process subsequent to FIG. 6A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as appropriate. Note that in each drawing, the size, length, thickness, distance, and ratio of each component may be exaggerated for the convenience of explanation.

[0020] [First embodiment] FIG. 1 is a diagram illustrating a main part of a method for manufacturing a double-sided metal-clad laminate according to a first embodiment of the present invention. FIG. 2 is an enlarged cross-sectional view of a coated pressure roll used in this method. In the method for manufacturing a double-sided metal-clad laminate according to this embodiment, a first metal-clad laminate 10 and an adhesive-layered metal-clad laminate 20A are superimposed and continuously passed between a pair of pressure rolls 40A and 40B, thereby thermocompressing the first metal-clad laminate 10 and the adhesive-layered metal-clad laminate 20A to manufacture a double-sided metal-clad laminate 100. Note that FIG. 1 illustrates only a portion of the long first metal-clad laminate 10 and the adhesive-layered metal-clad laminate 20A. Also, the arrows in FIG. 1 indicate the conveying direction and the rotation direction, and the unwinding roll, winding roll, guide roll, etc. are omitted. Also, the pair of pressure rolls 40A and 40B may each be equipped with a heating mechanism (not shown).

[0021] Although not shown, the first metal-clad laminate 10 is a single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on the first metal layer. The first metal-clad laminate 10 is formed in a long length and is transported in an orientation such that the first metal layer is in contact with the side in contact with the pressure roll 40A in FIG. The adhesive layer-attached metal-clad laminate 20A has a structure in which a second metal-clad laminate 20 and an adhesive layer 30 are laminated. Although not shown, the second metal-clad laminate 20 is a single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on the second metal layer. An adhesive layer 30 is laminated on the surface of the second metal-clad laminate 20 opposite the second metal layer. The adhesive layer-attached metal-clad laminate 20A is formed in a long length and is transported in an orientation such that the second metal layer contacts the side in contact with the pressure roll 40B in FIG. 1. The first metal-clad laminate 10 and the second metal-clad laminate 20 may have the same configuration or may have different configurations.

[0022] In Fig. 1, one pressure roll 40A is a metal roll having a coating layer 50, and the other pressure roll 40B is a metal roll not having a coating layer 50. Having one of the pressure rolls 40A, 40B as a coated pressure roll and the other roll as a metal roll not having a coating layer 50 and having a heating mechanism (not shown) is effective in efficiently transferring heat to the compression bonding site.

[0023] In Fig. 1, the pressure roll 40B on the adhesive layer-formed metal-clad laminate 20A side is a metal roll without a coating layer 50, but a metal roll without a coating layer 50 and having a heating mechanism (not shown) may be disposed on the first metal-clad laminate 10 side. In addition, both pressure rolls 40A, 40B may be coated pressure rolls having a coating layer 50. Using both pressure rolls 40A, 40B as coated pressure rolls is effective in preventing the occurrence of appearance defects such as wrinkles.

[0024] The covering layer 50 has the effect of alleviating bias in pressure during thermocompression bonding and distributing the pressure evenly, and has the effect of uniformly bonding the first metal-clad laminate 10 and the adhesive layer-attached metal-clad laminate 20A. The covering layer 50 is preferably formed of an elastic body such as silicone rubber, natural rubber, elastomer, fluororubber, or urethane. The hardness of the material constituting the covering layer 50 is preferably within the range of, for example, 60 to 90 degrees in spring hardness (JISA) based on the A-type spring hardness test according to JIS K6301 in order to ensure the function as a buffer material that distributes pressure evenly.

[0025] The thickness of the coating layer 50 is not particularly limited, but is preferably within the range of 1 to 50 mm, and more preferably within the range of 3 to 15 mm. The lower limit of the thickness of the coating layer 50 is preferably 3 mm or more to ensure the function as a buffer material that distributes pressure evenly, and the upper limit is preferably 15 mm or less to efficiently transmit heat.

[0026] Here, a preferred configuration example of the double-sided metal-clad laminate 100 manufactured by the method of the present embodiment will be described with reference to FIG. 3. FIG. 3 is a schematic diagram showing a cross-sectional structure of the double-sided metal-clad laminate 100. The double-sided metal-clad laminate 100 includes metal layers 101, 101 as the first metal layer and the second metal layer, polyimide layers 110, 110 as the first insulating resin layer and the second insulating resin layer, and an adhesive layer 30. Here, the metal layer 101 and the polyimide layer 110 are formed from the first metal-clad laminate 10 or the second metal-clad laminate 20, and the adhesive layer 30 is formed from the adhesive layer 30 of the adhesive layer-attached metal-clad laminate 20A. In FIG. 3, the symbol T1 indicates the total thickness of the double-sided metal-clad laminate 100, the symbol T2 indicates the thickness of the entire insulating resin laminate excluding the two metal layers 101 from the double-sided metal-clad laminate 100, and the symbol T3 indicates the thickness of the adhesive layer 30.

[0027] The thicknesses of the first insulating resin layer and the second insulating resin layer are both preferably within a range of, for example, 10 to 50 μm, and more preferably within a range of 12 to 38 μm. If the thicknesses of the first insulating resin layer and the second insulating resin layer are less than the above lower limit, problems such as warping of the double-sided metal-clad laminate 100 may occur. If the thicknesses of the first insulating resin layer and the second insulating resin layer exceed the above upper limit, problems such as reduced productivity may occur. Note that the first insulating resin layer and the second insulating resin layer do not necessarily have to be the same thickness.

[0028] The thickness T3 of the adhesive layer 30 is preferably within a range of, for example, 12 to 450 μm, more preferably within a range of 25 to 250 μm, and even more preferably within a range of 50 to 100 μm. If the thickness T3 of the adhesive layer 30 is less than the lower limit, the transmission loss as a high-frequency substrate may increase. On the other hand, if the thickness T3 of the adhesive layer 30 exceeds the upper limit, problems such as reduced dimensional stability may occur.

[0029] The total thickness T1 of the double-sided metal-clad laminate 100 may be, for example, 50 μm or more, preferably 50 to 200 μm, in order to improve the flexibility and bending resistance of the double-sided metal-clad laminate 100 and to reduce transmission loss in high-frequency transmission. The total thickness T2 of the insulating resin layers in the double-sided metal-clad laminate 100 may be, for example, 38 μm or more, preferably 50 to 200 μm, more preferably 50 to 150 μm, in order to reduce transmission loss in high-frequency transmission. The ratio (T3 / T2) of the thickness T3 of the adhesive layer 30 to the total thickness T2 of the insulating resin layers may be, for example, 0.3 to 0.8, preferably 0.5 to 0.8, in order to improve the dielectric properties by increasing the thickness of the insulating resin laminate while ensuring dimensional stability.

[0030] Examples of the material for the metal layer 101 include metals selected from copper, aluminum, stainless steel, iron, silver, palladium, nickel, chromium, molybdenum, tungsten, zirconium, gold, cobalt, titanium, tantalum, zinc, lead, tin, silicon, bismuth, indium, and alloys thereof. Copper and copper alloys are particularly preferred in terms of electrical conductivity.

[0031] Each of the polyimide layers 110, 110 may have a structure in which a plurality of polyimide layers are laminated. For example, in the embodiment shown in Fig. 3, a three-layer structure is formed with non-thermoplastic polyimide layers 111, 111 made of non-thermoplastic polyimide as a base layer, and thermoplastic polyimide layers 112, 112 made of thermoplastic polyimide provided on both sides of the non-thermoplastic polyimide layers 111, 111, respectively. Here, "non-thermoplastic polyimide" generally refers to polyimide that does not soften or exhibit adhesiveness even when heated. In the present invention, however, a non-thermoplastic polyimide having a storage modulus of 1.0 x 10 at 30°C measured using a dynamic viscoelasticity measuring device (DMA) is used. 9 Pa or more, and the storage modulus at 300°C is 3.0×10 8The term "thermoplastic polyimide" generally refers to a polyimide whose glass transition temperature (Tg) can be clearly confirmed. In the present invention, however, the term "thermoplastic polyimide" refers to a polyimide whose storage modulus at 30° C. is 1.0×10 Pa or more as measured using a dynamic viscoelasticity measuring device (DMA). 9 Pa or more, and the storage modulus at 320°C is 3.0×10 8 It refers to polyimide having a modulus of less than Pa. Note that each of the polyimide layers 110, 110 is not limited to a three-layer structure.

[0032] The polyimide used in the non-thermoplastic polyimide layer 111 is preferably a non-thermoplastic polyimide obtained by reacting an acid anhydride component containing an aromatic tetracarboxylic acid anhydride component with a diamine component containing an aliphatic diamine and / or an aromatic diamine, etc. As the acid anhydride component and the diamine component, monomers generally used in the synthesis of non-thermoplastic polyimides can be used. The polyimide used in the thermoplastic polyimide layer 112 is preferably a thermoplastic polyimide obtained by reacting an acid anhydride component containing an aromatic tetracarboxylic acid anhydride component with an aliphatic diamine and / or an aromatic diamine. As the acid anhydride and the diamine, monomers generally used in the synthesis of thermoplastic polyimides can be used. In the non-thermoplastic polyimide layer 111 and the thermoplastic polyimide layer 112, the thermal expansion, adhesion, glass transition temperature, etc. can be controlled by selecting the types of the above-mentioned acid anhydride components and diamine components, and by selecting the respective molar ratios when two or more types of acid anhydrides or diamines are used.

[0033] In the double-sided metal-clad laminate 100 shown in Figure 3, the outer thermoplastic polyimide layers 112, 112 of the first metal-clad laminate 10 and the second metal-clad laminate 20 are each bonded to an adhesive layer 30 to form the double-sided metal-clad laminate 100. The adhesive layer 30 is an adhesive layer for bonding the first metal-clad laminate 10 and the second metal-clad laminate 20 in the double-sided metal-clad laminate 100, and has the function of increasing the thickness T2 of the entire insulating resin laminate while ensuring dimensional stability, thereby improving the dielectric properties. The resin material constituting the adhesive layer 30 is not particularly limited, and may be composed of a thermoplastic resin or a thermosetting resin. Examples of such resins include polyimide resin, polyamide resin, epoxy resin, phenoxy resin, acrylic resin, polyurethane resin, styrene resin, polyester resin (including liquid crystal polyester resin), phenol resin, polysulfone resin, polyethersulfone resin, polyphenylene sulfide resin, polyethylene resin, polypropylene resin, silicone resin, polyether ketone resin, polyvinyl alcohol resin, polyvinyl butyral resin, styrene-maleimide copolymer, maleimide-vinyl compound copolymer, or (meth)acrylic copolymer, benzoxazine resin, bismaleimide resin, cyanate ester resin, etc.

[0034] The resin constituting the adhesive layer 30 is preferably a resin containing a thermoplastic polyimide as the main component of the resin component, more preferably 70% by weight or more of the resin component, even more preferably 90% by weight or more of the resin component, and most preferably the entire resin component contains a thermoplastic polyimide. The main component of the resin component means a component contained in more than 50% by weight of the total resin component. The preferred thermoplastic polyimide used for forming the adhesive layer 30 is a thermoplastic polyimide obtained by reacting an acid anhydride component containing an aromatic tetracarboxylic acid anhydride component with an aliphatic diamine and / or an aromatic diamine. As the acid anhydride and the diamine, a monomer generally used in the synthesis of a thermoplastic polyimide can be used, but a thermoplastic polyimide obtained by using a dimer diamine composition containing a dimer diamine as the main component, in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, in an amount of preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 80 to 99 mol % of the total diamine components is preferred. By using the dimer diamine composition in the above amount, it is possible to improve thermocompression bonding properties by lowering the glass transition temperature (lowering Tg) of the polyimide and to relieve internal stress by lowering the elastic modulus.

[0035] From the viewpoint of ensuring good adhesion, the adhesive layer 30 may have a storage modulus of 1800 MPa or less at 50° C. measured at a frequency of 11 Hz. The adhesive layer 30 may also have a thermal expansion coefficient of 110 ppm / K. In order to continuously bond the adhesive layer 30, which is thus highly flexible, has a large thermal expansion coefficient, and has a relatively large thickness T3, to the first metal-clad laminate 10, which has a relatively small thermal expansion coefficient, by a roll-to-roll method, the manufacturing method of this embodiment employs the following thermocompression bonding conditions.

[0036] <Thermocompression bonding conditions> 2, in order to prevent wrinkles, the distance (clearance) L between the pressure rolls 40A and 40B is adjusted to within a range of 70% to 97%, preferably 80% to 97%, of the total thickness T1 of the double-sided metal-clad laminate 100. The wrinkles are likely caused by the fact that the adhesive-layered metal-clad laminate 20A, which has a low storage modulus, a large thermal expansion coefficient, and a thick adhesive layer 30, is continuously conveyed together with the first metal-clad laminate 10, which has a relatively small thermal expansion coefficient, causing bending in the first metal-clad laminate 10 and / or the adhesive-layered metal-clad laminate 20A, and the bending is rolled up during thermocompression bonding. Generally, when manufacturing a double-sided metal-clad laminate having a total thickness of less than 50 μm, the distance L between the pressure rolls 40A, 40B is often set to 0 μm. However, in this embodiment, the distance L is adjusted to the above range taking into account the total thickness T1 of the double-sided metal-clad laminate 100, and excessive pressure is not applied to the first metal-clad laminate 10 and the adhesive layer-coated metal-clad laminate 20A, which are the materials to be bonded, during thermocompression bonding, thereby allowing deflection to escape and effectively preventing the occurrence of wrinkles. Note that the distance L is the distance between the surface of the pressure roll 40A and the surface of the coating layer 50 of the pressure roll 40B, and means the distance measured at both axial ends of the pressure rolls 40A, 40B before the pressure rolls 40A, 40B are heated.

[0037] The pressure when the first metal-clad laminate 10 and the adhesive-layered metal-clad laminate 20A are thermocompression-bonded by the pressure rolls 40A and 40B is not particularly limited, but from the viewpoint of preventing the occurrence of wrinkles, it is preferable to set it to, for example, 1.0 MPa or less, and more preferably within the range of 0 to 0.5 MPa. As described above, the occurrence of wrinkles is considered to be caused by the fact that the adhesive-layered metal-clad laminate 20A having a low storage modulus, a large thermal expansion coefficient, and a thick adhesive layer 30 is continuously conveyed with the first metal-clad laminate 10 having a relatively small thermal expansion coefficient, causing bending in the first metal-clad laminate 10 and / or the adhesive-layered metal-clad laminate 20A, and this bending is rolled in during thermocompression bonding. Therefore, by adjusting the pressure applied to the first metal-clad laminate 10 and the adhesive-layered metal-clad laminate 20A, which are the materials to be thermocompressed during thermocompression bonding, to 1.0 MPa or less, the bending can be released and the occurrence of wrinkles can be prevented. The pressure during thermocompression bonding is the average pressure in the axial direction of the pressure rolls 40A and 40B. The pressure method is not particularly limited as long as it can apply a predetermined pressure, and examples of the pressure method include a hydraulic method, a pneumatic method, and a gap pressure method.

[0038] The temperature during thermocompression bonding is preferably, for example, 50° C. or higher, and more preferably within the range of 60 to 130° C. The method for heating the pressure rolls 40A and 40B is not particularly limited, and examples thereof include a heat medium circulation method, a hot air heating method, and a dielectric heating method. The temperature during thermocompression bonding refers to the temperature of the surface of a metal roll having a heating mechanism.

[0039] The insertion angle θ1 of the first metal-clad laminate 10 into the pressure roll 40A during thermocompression bonding is not particularly limited, but is preferably within a range of, for example, 3 to 45° because the warp of the double-sided metal-clad laminate 100 caused by thermal expansion is easily expanded. Also, the insertion angle (not shown) of the adhesive layer-formed metal-clad laminate 20A into the pressure roll 40B during thermocompression bonding is not particularly limited, but is preferably within a range of, for example, 3 to 45° because the warp of the double-sided metal-clad laminate 100 caused by thermal expansion is easily expanded. In addition, the insertion angle θ1 of the first metal-clad laminate 10 into the pressure roll 40A means the angle that the first metal-clad laminate 10 makes with respect to the tangent direction at the location (contact point) where the first metal-clad laminate 10 and the pressure roll 40A having a circular cross-section come into contact, and the insertion angle (not shown) of the adhesive layer-coated metal-clad laminate 20A into the pressure roll 40B means the angle that the adhesive layer-coated metal-clad laminate 20A makes with the tangent direction at the location (contact point) where the adhesive layer-coated metal-clad laminate 20A and the pressure roll 40B having a circular cross-section come into contact.

[0040] 4 is an explanatory diagram showing an example of a manufacturing process of the double-sided metal-clad laminate of the present embodiment. In this embodiment, the adhesive layer-attached metal-clad laminate 20A is obtained through a process of applying and drying a resin composition to the surface of the second metal-clad laminate 20 opposite the second metal layer to form an adhesive layer 30.

[0041] The second metal-clad laminate 20 is formed in a long length and is configured to be transported by a roll-to-roll method. That is, in this embodiment, the long second metal-clad laminate 20 is formed so as to be transportable between an unwinding roll 201 and a winding roll 202. While the second metal-clad laminate 20 is transported by a roll-to-roll method, a solution-like resin composition S to become the adhesive layer 30 is applied to the second insulating resin layer side by an application device 210. When the adhesive layer 30 is made of polyimide, a polyimide solution or a polyamic acid solution can be used as the resin composition S. The applied resin composition S is heated and dried in a heating section 220 to become the adhesive layer 30. In this way, the adhesive layer-attached metal-clad laminate 20A is produced during the transport and is transported to a pair of pressure rolls 40A and 40B. Meanwhile, just before the pressure rolls 40A, 40B, a first metal-clad laminate 10 is supplied from a supply roll 230, and the first metal-clad laminate 10 and the adhesive layer-provided metal-clad laminate 20A are thermocompression-bonded and laminated by the pressure rolls 40A, 40B to produce a double-sided metal-clad laminate 100. The double-sided metal-clad laminate 100 is taken up by a take-up roll 202 and collected as a product.

[0042] In the manufacturing process illustrated in FIG. 4, the distance L between the pressure rolls 40A and 40B is adjusted to within a range of 70% to 97% of the total thickness T1 of the double-sided metal-clad laminate 100, and excessive pressure is not applied to the first metal-clad laminate 10 and the adhesive layer-attached metal-clad laminate 20A during thermocompression bonding, thereby effectively preventing the occurrence of wrinkles. Therefore, according to the manufacturing method of this embodiment, it is possible to efficiently manufacture a double-sided metal-clad laminate 100 that is wrinkle-free and has a good appearance, and the productivity of the double-sided metal-clad laminate 100 can be increased. In addition, the double-sided metal-clad laminate 100 manufactured by the method of this embodiment not only has a good appearance because wrinkles are prevented from occurring, but also contributes to improving the reliability of the circuit board obtained by circuit processing the double-sided metal-clad laminate 100.

[0043] [Second embodiment] FIG. 5 is a diagram illustrating a main part of a method for manufacturing a double-sided metal-clad laminate according to a second embodiment of the present invention. In the method for manufacturing a double-sided metal-clad laminate 100 of this embodiment, a first metal-clad laminate 10, an adhesive sheet 30A, and a second metal-clad laminate 20 are stacked in this order and continuously passed between a pair of pressure rolls 40A and 40B to thermocompress the first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20 to manufacture the double-sided metal-clad laminate 100. Note that FIG. 5 illustrates only a portion of the long first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20. Also, the arrows in FIG. 5 indicate the conveying direction and the rotation direction, and the unwinding roll, the winding roll, the guide roll, and the like are omitted from the illustration.

[0044] In this embodiment, the configurations of the first metal-clad laminate 10, the second metal-clad laminate 20, the pair of pressure rolls 40A, 40B, and the double-sided metal-clad laminate 100 are the same as those of the first embodiment. The adhesive sheet 30A is a self-supporting film, and its material, thickness, physical properties, etc. are the same as those of the adhesive layer 30 in the first embodiment. The first metal-clad laminate 10 is conveyed in an orientation such that the first metal layer is in contact with the pressure roll 40A in FIG. 5. The second metal-clad laminate 20 is conveyed in an orientation such that the second metal layer is in contact with the pressure roll 40B in FIG. 5. Then, the first metal-clad laminate 10 and the second metal-clad laminate 20 are laminated by laminating them so that the adhesive sheet 30A is interposed between them and passing them continuously between the pair of pressure rolls 40A, 40B to produce the double-sided metal-clad laminate 100.

[0045] The thermocompression bonding conditions for laminating the first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20 are the same as those in the first embodiment. 2, the distance (clearance) L between the pressure rolls 40A and 40B is adjusted to within a range of 70% to 97%, preferably 80% to 97%, of the total thickness T1 of the double-sided metal-clad laminate 100 in order to prevent wrinkles. The wrinkles are likely caused by the fact that the adhesive sheet 30A, which has a low storage modulus, a large thermal expansion coefficient, and a large thickness, is continuously conveyed together with the first metal-clad laminate 10 and the second metal-clad laminate 20, which have relatively small thermal expansion coefficients, causing bending of the first metal-clad laminate 10 and / or the second metal-clad laminate 20, and this bending is rolled up during thermocompression bonding. Generally, when manufacturing a double-sided metal-clad laminate with a total thickness of less than 50 μm, the distance L between the pressure rolls 40A, 40B is often set to 0 μm. However, in this embodiment, the distance L is adjusted to the above range taking into account the total thickness T1 of the double-sided metal-clad laminate 100, and excessive pressure is not applied to the materials to be pressed, that is, the first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20, during thermocompression bonding, thereby allowing deflection to escape and effectively preventing the occurrence of wrinkles. The distance L means the distance measured between both ends of the pressure rolls 40A, 40B in the axial direction before the pressure rolls 40A, 40B are heated.

[0046] The pressure applied by the pressure rolls 40A and 40B during the thermocompression bonding of the first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20 is not particularly limited, but from the viewpoint of preventing the occurrence of wrinkles, it is preferably 1.0 MPa or less, and more preferably in the range of 0 to 0.5 MPa. As described above, the occurrence of wrinkles is considered to be caused by the adhesive sheet 30A, which has a low storage modulus, a large thermal expansion coefficient, and a large thickness, being continuously conveyed with the first metal-clad laminate 10 and the second metal-clad laminate 20, which have a relatively small thermal expansion coefficient, causing the first metal-clad laminate 10 and / or the second metal-clad laminate 20 to be warped, and the warp is rolled in during thermocompression bonding. Therefore, by adjusting the pressure applied to the first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20, which are the materials to be compressed during thermocompression bonding, to 1.0 MPa or less, the warp is released and the occurrence of wrinkles can be prevented. The pressure during thermocompression bonding is the average pressure in the axial direction of the pressure rolls 40A and 40B. The pressure method is not particularly limited as long as it can apply a predetermined pressure, and examples of the pressure method include a hydraulic method, a pneumatic method, and a gap pressure method.

[0047] The temperature during thermocompression bonding is, for example, preferably 50°C or higher, and more preferably within the range of 60 to 130°C.

[0048] The insertion angle θ2 of the first metal-clad laminate 10 to the pressure roll 40A during thermocompression bonding is not particularly limited, but is preferably in the range of, for example, 3 to 45°, because this makes it easy for the deflection of the double-sided metal-clad laminate 100 caused by thermal expansion to widen. In addition, the insertion angle θ3 of the second metal-clad laminate 20 to the pressure roll 40B during thermocompression bonding is not particularly limited, but it is preferable to set it in the range of, for example, 3 to 45°, because this makes it easy for the deflection of the double-sided metal-clad laminate 100 caused by thermal expansion to widen. Furthermore, the insertion angle (not shown) of the adhesive sheet 30A into the pressure roll 40B during thermocompression bonding is not particularly limited, but is preferably within the range of, for example, 3 to 45°, because this makes it easy for the deflection of the double-sided metal-clad laminate 100 caused by thermal expansion to widen. The insertion angle θ2 of the first metal-clad laminate 10 into the pressure roll 40A means the angle of the first metal-clad laminate 10 with respect to the tangent direction at the contact point (contact point) between the first metal-clad laminate 10 and the pressure roll 40A having a circular cross section, and the insertion angle θ3 of the second metal-clad laminate 20 into the pressure roll 40B means the angle of the second metal-clad laminate 20 with respect to the tangent direction at the contact point (contact point) between the second metal-clad laminate 20 and the pressure roll 40B having a circular cross section. The insertion angle (not shown) of the adhesive sheet 30A into the pressure roll 40B means the angle of the adhesive sheet 30A with respect to the tangent direction at the contact point (contact point) between the second metal-clad laminate 20 and the pressure roll 40B having a circular cross section.

[0049] 6A and 6B are explanatory diagrams showing an example of a manufacturing process for the double-sided metal-clad laminate of the present embodiment. In this embodiment, an adhesive sheet 30A is obtained through a process of applying and drying a resin composition S to a substrate to form a self-supporting film, and a process of peeling the self-supporting film from the substrate.

[0050] First, as shown in FIG. 6A, the release film 30B as the substrate is formed in a long length and is configured to be transported by a roll-to-roll method. That is, the long release film 30B is formed so as to be transportable between an unwinding roll 203 and a winding roll 204. While the release film 30B is transported by the roll-to-roll method, a solution-like resin composition S that becomes the adhesive sheet 30A is applied to one side of the release film 30B by an application device 210 to form a coated release film 30C. When the adhesive sheet 30A is made of polyimide, a polyimide solution or a polyamic acid solution can be used as the resin composition S.

[0051] The release film with the coating film 30C passes through the heating section 220, whereby the coating film is heated and dried, and becomes the release film with the adhesive layer 30D on which the self-supporting adhesive sheet 30A is formed. Next, the protective film 30E is supplied from the supply roll 240, and the protective film 30E is temporarily pressure-bonded to the adhesive layer 30 side of the release film with the adhesive layer 30D by the pressure rolls 40C and 40D, and is collected by the take-up roll 204 as the adhesive sheet with the protective film 30F.

[0052] FIG. 6B shows a process following FIG. 6A. As shown in FIG. 6B, the long protective film-attached adhesive sheet 30F is transported from the unwinding roll 205 to the winding roll 206. On the way, the protective film 30E and the release film 30B are peeled off to form a self-supporting adhesive sheet 30A. The protective film 30E and the release film 30B are collected by the winding rolls 208 and 209, respectively. Next, while the self-supporting adhesive sheet 30A is being transported, the first metal-clad laminate 10 supplied from the supply roll 250 is laminated on one side of the sheet by a pair of pressure rolls 40A and 40B, and the second metal-clad laminate 20 supplied from the supply roll 260 is laminated on the other side of the sheet by thermocompression bonding. The double-sided metal-clad laminate 100 is then manufactured by laminating the two sheets by the pair of pressure rolls 40A and 40B. The double-sided metal-clad laminate 100 is wound by the winding roll 206 and collected as a product.

[0053] 6A and 6B may be carried out consecutively without including the steps of recovering the adhesive sheet 30F with a protective film onto the winding roll 204 and transporting it from the unwinding roll 205.

[0054] In the manufacturing process illustrated in FIG. 6A and FIG. 6B, the distance L between the pressure rolls 40A and 40B is adjusted to within a range of 70% to 97% of the total thickness T1 of the double-sided metal-clad laminate 100, and excessive pressure is not applied to the first metal-clad laminate 10, the adhesive sheet 30A, and the second metal-clad laminate 20 during thermocompression bonding, thereby effectively preventing the occurrence of wrinkles. Therefore, according to the manufacturing method of this embodiment, it is possible to efficiently manufacture a double-sided metal-clad laminate 100 that is wrinkle-free and has a good appearance, and the productivity of the double-sided metal-clad laminate 100 can be increased. In addition, the double-sided metal-clad laminate 100 manufactured by the method of this embodiment not only has a good appearance because wrinkles are prevented from occurring, but also contributes to improving the reliability of the circuit board obtained by circuit processing the double-sided metal-clad laminate 100. Other configurations and effects of the second embodiment are similar to those of the first embodiment. EXAMPLES

[0055] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.

[0056] [Measurement of coefficient of thermal expansion (CTE)] A sample of 3 mm x 20 mm was cut out from the adhesive film, and using a thermomechanical analyzer (manufactured by Bruker, product name: 4000SA), the sample was heated from 30°C to 265°C at a constant heating rate while applying a load of 5.0 g, and then held at that temperature for 10 minutes. The sample was then cooled at a rate of 5°C / min, and the average thermal expansion coefficient (linear thermal expansion coefficient) from 240°C to 100°C was determined.

[0057] [Measurement of storage modulus] The storage modulus was measured by cutting a 5 mm x 20 mm piece from the adhesive film and heating it in an oven at 120°C for 2 hours and at 170°C for 3 hours. The obtained sample was heated stepwise from 30°C to 400°C at a heating rate of 4°C / min using a dynamic viscoelasticity device (DMA: manufactured by UBM, product name: E4000F) and measured at a frequency of 11 Hz.

[0058] [Observation of adhesion state] The single-sided copper-clad laminate was peeled off over its entire width from the double-sided copper-clad laminate after thermocompression bonding, and the adhesive film surface was visually observed. Films with a uniform color tone over the entire surface were rated as having "good" overall adhesion, and films with areas of different color tone were rated as having "poor" adhesion.

[0059] [Method for measuring amine value] Approximately 2 g of the dimer diamine composition is weighed into a 200-250 mL Erlenmeyer flask, and phenolphthalein is used as an indicator. A 0.1 mol / L ethanolic potassium hydroxide solution is dropped into the solution until the solution turns light pink, and the solution is dissolved in approximately 100 mL of neutralized butanol. 3-7 drops of phenolphthalein solution are added thereto, and titration is performed with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Five drops of bromophenol blue solution are added thereto, and titration is performed with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow. The amine value is calculated according to the following formula (1). Amine value = {(V2 x C2) - (V1 x C1)} x M KOH / m (1) Here, the amine value is expressed as mg-KOH / g, and M KOH is the molecular weight of potassium hydroxide, 56.1. V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent a 0.1 mol / L ethanolic potassium hydroxide solution and a 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight in grams.

[0060] [Calculation of GPC and chromatogram area percentage] (a) Dimer diamine (b) A monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group. (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine).

[0061] For GPC, 20 mg of the dimer diamine composition was pretreated with 200 μL of acetic anhydride, 200 μL of pyridine, and 2 mL of tetrahydrofuran (THF) to prepare 100 mg of solution, which was then diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a Tosoh Corporation product name: HLC-8220GPC under the following conditions: column: TSK-gel G2000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40° C., injection volume: 50 μL. Cyclohexanone was used as a standard substance to correct the elution time.

[0062] In this case, the retention times were adjusted so that the peak top of the cyclohexanone main peak was at a retention time of 27 to 31 minutes, and the period from the peak start to the peak end of the cyclohexanone main peak was 2 minutes, and the peak top of the main peak excluding the cyclohexanone peak was at a retention time of 18 to 19 minutes, and the period from the peak start to the peak end of the main peak excluding the cyclohexanone peak was 2 minutes to 4 minutes 30 seconds. (a) Component represented by the main peak; (b) A component represented by a GPC peak detected at a time later than the minimum retention time of the main peak; (c) Components represented by GPC peaks detected at earlier retention times than the minimum value of the main peak on the earlier side; was detected.

[0063] [Viscosity measurement] Using an E-type viscometer (DV-II+ProCP type), the viscosity of the polyimide solution immediately after polymerization was measured under the conditions of a temperature of 25° C., a rotation speed of 100 RPM, and a measurement time of 2 minutes.

[0064] [Measurement of weight average molecular weight (Mw) of polyimide] The weight average molecular weight was measured by gel permeation chromatography (HLC-8220GPC, manufactured by Tosoh Corporation). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.

[0065] The abbreviations used in the examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride DDA: Croda Japan Co., Ltd. (product name: distilled and purified PRIAMINE 1075 (component a: 99.2%, component b: 0%, component c: 0.8%, amine value: 210 mg KOH / g) N-12: Dodecanedioic acid dihydrazide NMP: N-methyl-2-pyrrolidone In the above DDA, the "%" of component a, component b, and component c means the area percentage of the chromatogram in GPC measurement. The molecular weight of the above DDA was calculated by the following formula. Molecular weight = 56.1 x 2 x 1000 / amine value

[0066] (Synthesis Example 1) In a reaction vessel equipped with a thermocouple and a stirrer and capable of introducing nitrogen, 44.98 g of BTDA (0.139 mol), 75.02 g of DDA (0.140 mol), 168 g of NMP, and 112 g of xylene were charged and mixed thoroughly at 40°C for 1 hour to prepare a polyamic acid solution. This polyamic acid solution was heated to 190°C and stirred with heating for 5 hours, and 112 g of xylene was added to complete the imidization, preparing polyimide adhesive solution 1. The solid content of the obtained polyimide adhesive solution 1 was 29.1% by weight, and the viscosity was 7,800 cps. The weight average molecular weight (Mw) of the polyimide was 87,700.

[0067] (Synthesis Example 2) Polyimide adhesive solution 2 was prepared by mixing 34.4 g (10 g as solid content) of polyimide adhesive solution 1 obtained in Synthesis Example 1 with 1.25 g of N-12 and 2.5 g of Exolit OP935 (trade name, Clariant Japan Ltd., aluminum diethylphosphinate), and diluting with the addition of 1.297 g of NMP and 3.869 g of xylene.

[0068] (Example 1) The polyimide adhesive solution 1 was applied to one side of a long release PET film 1 (Higashiyama Film Co., Ltd., product name: HY-S05, thickness: 25 μm) so that the thickness after drying would be 50 μm, and the film was dried by heating stepwise from 80°C to 160°C to remove the solvent, and the adhesive layer was peeled off from the release PET film 1 to obtain an adhesive film 1 with a thickness of 50 μm. The CTE of the adhesive film 1 was 95 ppm / K and the storage modulus was 1220 MPa.

[0069] (Example 2) Except for coating so that the thickness after drying was 75 μm, an adhesive film 2 having a thickness of 75 μm was obtained in the same manner as in Preparation Example 1. The adhesive film 2 had a CTE of 95 ppm / K and a storage modulus of 1220 MPa.

[0070] [Example 1] The polyimide adhesive solution 2 prepared in Synthesis Example 2 was continuously and uniformly applied to the insulating resin layer side of a long single-sided metal-clad laminate 1a (manufactured by Nippon Steel Chemical & Materials Co., Ltd., product name: Espanex FC12-25-00UEJ, electrolytic copper foil thickness: 12 μm, insulating resin layer thickness: 25 μm, width: 530 mm) using a die coater so that the thickness after drying would be 50 μm.Then, the solution was dried by heating in stages from 80°C to 160°C to remove the solvent, and a single-sided metal-clad laminate with an adhesive layer 1a' was obtained.

[0071] Next, the adhesive layer side of the single-sided metal-clad laminate 1a' with adhesive layer and the insulating resin layer side of the other single-sided metal-clad laminate 1a are arranged so as to be in contact with each other, and these are continuously superimposed and continuously thermocompressed while being transported via guide rolls using a heating and pressing device having at least one pair of metallic heating and pressing rolls and a roll covered with silicone rubber (thickness: 10 mm) to obtain a double-sided copper-clad laminate 1. The double-sided copper-clad laminate 1 was free of wrinkles and had good overall adhesion. The thermocompression conditions are as follows. Here, the lamination pressure refers to the pressure from a cylinder applied to both ends of a pair of lamination rolls. Distance between the metal heating and pressure roll surface and the silicone rubber-coated surface (L): 120 μm Roll surface temperature: 100℃ Lamination pressure: 0.5MPa Conveying speed: 2.0m / min Insertion angle of adhesive layered single-sided metal-clad laminate 1a' into metal heating and pressurizing roll: 45° Insertion angle of single-sided metal-clad laminate 1a into silicone rubber-coated roll: 45°

[0072] [Example 2] Except for changing the value of L to 100 μm, a double-sided copper-clad laminate 2 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 2 had no wrinkles and good overall adhesion.

[0073] [Example 3] Except for changing the lamination pressure to 0.1 MPa, the same procedure as in Example 1 was followed to obtain a double-sided copper-clad laminate 3. The double-sided copper-clad laminate 3 had no wrinkles and good overall adhesion.

[0074] [Example 4] Except for setting the value of L to 100 μm and the lamination pressure to 0.1 MPa, a double-sided copper-clad laminate 4 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 4 had no wrinkles and good overall adhesion.

[0075] [Example 5] Except for adjusting the thickness of the polyimide adhesive solution 2 after drying to 75 μm, a double-sided copper-clad laminate 5 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 5 had no wrinkles and good overall adhesion.

[0076] [Example 6] Except for the fact that the thickness of the polyimide adhesive solution 2 after drying was 75 μm and the lamination pressure was 0.1 MPa, a double-sided copper-clad laminate 6 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 6 had no wrinkles and good overall adhesion.

[0077] [Example 7] Two long single-sided metal-clad laminates 1a were arranged so that the insulating resin layer faces of the two laminates were in contact with both sides of the adhesive film 1, and these were continuously superimposed and thermocompressed using a heating and pressing device having at least one pair of a metallic heating and pressing roll and a roll covered with silicone rubber (thickness: 10 mm) while being transported through a guide roll, to obtain a double-sided copper-clad laminate 7. The double-sided copper-clad laminate 7 had no wrinkles and good overall adhesion. The thermocompression bonding conditions were as follows. Distance between the metal heating and pressure roll surface and the silicone rubber-coated surface (L): 120 μm Roll surface temperature: 100℃ Lamination pressure: 0.5MPa Conveying speed: 2.0m / min Insertion angle of the single-sided metal-clad laminate 1a into the metal heating and pressing roll: 45° Insertion angle of adhesive film 1 into metal heating and pressure roll: 3° Insertion angle of single-sided metal-clad laminate 1a into silicone rubber-coated roll: 45°

[0078] [Example 8] A double-sided copper-clad laminate 8 was obtained in the same manner as in Example 7, except that Adhesive Film 2 was used instead of Adhesive Film 1. The double-sided copper-clad laminate 8 had no wrinkles and good overall adhesion.

[0079] Comparative Example 1 Except for setting the value of L to 0 μm, a double-sided copper-clad laminate 9 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 9 had good overall adhesion, but wrinkles were generated.

[0080] Comparative Example 2 Except for setting the value of L to 0 μm and the lamination pressure to 0.1 MPa, a double-sided copper-clad laminate 10 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 10 had good overall adhesion, but wrinkles occurred.

[0081] Comparative Example 3 Except for changing the value of L to 80 μm, a double-sided copper-clad laminate 11 was obtained in the same manner as in Example 1. The double-sided copper-clad laminate 11 had good overall adhesion, but wrinkles were generated.

[0082] Comparative Example 4 Except for changing the value of L to 125 μm, a double-sided copper-clad laminate 12 was obtained in the same manner as in Example 1. There were no wrinkles in the double-sided copper-clad laminate 12, but the overall adhesion was poor.

[0083] As described above in detail, the method for producing a metal-clad laminate according to the present embodiment produces a double-sided metal-clad laminate with good appearance and full adhesion. By using the double-sided metal-clad laminate produced in this manner as a circuit board material for FPCs and the like, circuit boards with excellent adhesion and reliability can be produced with good yield. Thus, the present invention can improve the yield and reliability of circuit boards and electronic products that use circuit boards.

[0084] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment. [Explanation of symbols]

[0085] 10...first metal-clad laminate, 20...second metal-clad laminate, 20A...metal-clad laminate with adhesive layer, 30...adhesive layer, 30A...adhesive sheet, 30B...release film, 30C...release film with coating film, 30D...release film with adhesive layer, 30E...protective film, 30F...adhesive sheet with protective film, 40A, 40B...pressure roll, 50...covering layer, 80A, 80B...guide roll, 100...double-sided metal-clad laminate, 101...metal layer, 110...polyimide layer, 111...non-thermoplastic polyimide layer, 112...thermoplastic polyimide layer, 201, 203, 205...unwinding roll, 202, 204, 206, 208, 209...winding roll, 210...coating device, 220...heating section, 230, 240, 250, 260...supply roll

Claims

1. A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on one surface of the first metal layer; a single-sided metal-clad laminate having an adhesive layer, the single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on one side of the second metal layer, the single-sided metal-clad laminate having an adhesive layer laminated on the side opposite the second metal layer; The method for producing a double-sided metal-clad laminate includes laminating the first insulating resin layer and the adhesive layer so that the first insulating resin layer and the adhesive layer are in contact with each other and continuously passing the laminate between a pair of laminating rolls, The thickness of the adhesive layer is in the range of 12 to 450 μm, The insertion angle of the first single-sided metal-clad laminate with respect to one of the lamination rolls is within a range of 3 to 45 degrees, the insertion angle of the adhesive layer-attached single-sided metal-clad laminate with respect to the other lamination roll is within a range of 3 to 45°; A method for producing a double-sided metal-clad laminate, comprising adjusting the distance between the pair of lamination rolls to within a range of 70% to 97% of the thickness of the double-sided metal-clad laminate.

2. The method for producing a double-sided metal-clad laminate described in claim 1, wherein the single-sided metal-clad laminate with adhesive layer is obtained by applying and drying a resin composition to the side opposite the second metal layer of the second single-sided metal-clad laminate to form the adhesive layer.

3. A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on one surface of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on one surface of the second metal layer; a self-supporting adhesive film; and laminating the first insulating resin layer and the second insulating resin layer so that the adhesive film is interposed between the first insulating resin layer and the second insulating resin layer by continuously passing the laminate between a pair of laminating rolls, thereby producing a double-sided metal-clad laminate, The thickness of the adhesive film is within the range of 12 to 450 μm, The insertion angle of the first single-sided metal-clad laminate with respect to one of the lamination rolls is within a range of 3 to 45 degrees, The insertion angle of the second single-sided metal-clad laminate relative to the other lamination roll is within a range of 3 to 45 degrees, A method for producing a double-sided metal-clad laminate, comprising adjusting the distance between the pair of lamination rolls to within a range of 70% to 97% of the thickness of the double-sided metal-clad laminate.

4. The adhesive film is applying a resin composition to a substrate and drying the composition to form a self-supporting film; peeling the self-supporting film from the substrate; The method for producing a double-sided metal-clad laminate according to claim 3, wherein the laminate is obtained through the steps of:

5. The method for producing a double-sided metal-clad laminate according to claim 1 , wherein the pressure applied by the pair of laminating rolls is 1.0 MPa or less.

6. 6. The method for producing a double-sided metal-clad laminate according to claim 1, wherein at least one of the pair of laminating rolls is a covered roll having a covering layer made of an elastic material on the surface of a metal roll.

Citation Information

Patent Citations

  • Graphene-based flexible electrode and preparation method thereof

    CN109841426A

  • Method of manufacturing flexible laminated product

    JP1980014210A

  • Device for laminating pattern printing film

    JP2002337233A

  • Method for manufacturing laminate

    JP2004358678A

  • Method and equipment for manufacturing laminate

    JP2005059486A